Development of Teaching Materials for Study of Prose Fiction Based on Simalungun Local Wisdom Indonesian Language Education Students UHKBPNP - Monalisa Frince S; Daulat Nathanael Banjarnahor (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine: (1) the preparation of development of teaching materials for the study of prose fiction based on local wisdom simalungun, (2) the feasibility of teaching materials for the study of prose fiction based on local wisdom simalungun, (3) the effectiveness of teaching materials for the study of prose fiction based on local wisdom simalungun education students’ Indonesian language University HKBP Nommensen Pematangsiantar. This type of research is research and development based on the Borg and Gall development model. The trial subjects consisted of material experts, design experts, Indonesian language education lecturers, Indonesian language education students. Data on the quality of these products are collected through questionnaires and essay tests. The results of this study indicate that: (1) material validation includes content feasibility with an average of 92.96% on very good criteria, presentation feasibility with an average of 92.30% on very good criteria, language eligibility with an average of 90, 38% on very good criteria, (2) validation of design experts with an average of 87.91% on very good criteria, (3) individual trials with an average of 82.50% with very good criteria, (4) trials small group with an average of 83.33% with very good criteria, and (5) limited field group test with an average of 90.83% with very good criteria, (6) the effectiveness of teaching materials shows a posttest presentation of 80.35 more higher than the pretest presentation of 68.11. Thus, teaching materials for the study of prose fiction based on local wisdom Simalungun that have been developed are feasible and effective to be used as learning resources.